From stigma to support: Assessing the impact of school mental health literacy program in Addis Ababa, Ethiopia - Lidia Veliaminova; Surafel Worku Megersa; Finina Abebe Ware; Paula Gerbig; Sandra Dehning; Eshetu Girma; Andrea Jobst (PLOS Global Public Health, 2026)
Mental health stigma remains a major barrier due to limited mental health promotion and care among adolescents in low- and middle-income countries (LMICs), due to a lack of mental health literacy, sociocultural beliefs, and misconceptions which contribute to delayed help-seeking and poor mental health outcomes. In Ethiopia, stigma surrounding mental illness can result in social exclusion, discrimination, and abandonment by family members. This study evaluated the effectiveness of a culturally adapted, school-based mental health literacy and anti-stigma intervention among secondary school students in Addis Ababa, Ethiopia. The intervention was culturally adapted in collaboration with local mental health experts and adolescent students to ensure relevance to the Ethiopian context. Using a train-the-trainer approach, seven school nurses and health extension workers were trained to deliver the intervention to 186 students across four secondary schools. Implemented over one week, the intervention utilized three components: (1) an interactive mental health literacy curriculum delivered through PowerPoint presentations and participatory activities, (2) a contact-based session involving a person with lived experience of mental illness, and (3) mental health promotion materials, including posters and bookmarks displaying anti-stigma messages. Outcomes were assessed using self-administered questionnaires completed before the intervention and three weeks after its completion. Following the intervention, students demonstrated improved mental health knowledge and more positive attitudes toward mental illness (t(185) = 8.67, p < 0.001). Social distance, avoidance, and discomfort toward individuals with mental health problems were reduced, while intentions to seek help increased, with participants reporting greater willingness to seek support from formal and informal sources. These findings suggest that a culturally adapted, school-based mental health literacy and anti-stigma intervention was associated with improving adolescents’ mental health knowledge, reduce stigmatizing attitudes, and strengthening help-seeking intentions. Such interventions represent a promising strategy for supporting adolescent mental health and addressing stigma in Ethiopia and other LMIC settings.